Partial lipodystrophy with renal disorder - Saraçlar, Yıldız; Tınaztepe, Behçet; Çoruh, Mithat; Erkoçak, Deniz (The Turkish Journal of Pediatrics, 1972)
An 8-year-old girl with partial lipodystrophy with renal involvement is reported. The diagnosis of our patient is confirmed by skin and renal biopsies. The impression of the kidney biopsy was glomerulonephritis, suggestive of autoimmunization or hypersensitivity reaction.We found only 28 similar cases in the world literature. To our knowledge this is the first report from Turkey.A possible pathogenesis of the disease is also speculated.